2014
DOI: 10.1007/s10967-014-3815-5
|View full text |Cite
|
Sign up to set email alerts
|

Californium purification and electrodeposition

Abstract: The staff at the Radiochemical Engineering Development Center, located at Oak Ridge National Laboratory, produced a 6.3 ± 0.4 GBq (1.7 ± 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…A signicant amount of iodine has been observed in the outlet end of the furnace tube when a long outlet end was applied. 31 An extra heating wire wrapped around the outlet part of the furnace tube has been proposed to solve this problem. 26,29 The approach of shortening the outlet end of the furnace tube and maintaining a high temperature in the second zone of the furnace from the beginning of the combustion until the end is proposed in this work, which is simple and easy to operate.…”
Section: Reliable Ignition Of Vegetation In the Pyrolysis Processmentioning
confidence: 99%
See 3 more Smart Citations
“…A signicant amount of iodine has been observed in the outlet end of the furnace tube when a long outlet end was applied. 31 An extra heating wire wrapped around the outlet part of the furnace tube has been proposed to solve this problem. 26,29 The approach of shortening the outlet end of the furnace tube and maintaining a high temperature in the second zone of the furnace from the beginning of the combustion until the end is proposed in this work, which is simple and easy to operate.…”
Section: Reliable Ignition Of Vegetation In the Pyrolysis Processmentioning
confidence: 99%
“…Our 125 I tracer experiment has shown that only a small fraction of iodine (<2%) was vaporized from the samples and collected in the trap solution below 400 C. A combustion temperature range of 800-1000 C has been used for the vaporization of iodine from solid samples (soil, sediment, and vegetation). [17][18][19]22,[26][27][28][29][30][31] It has been reported that the remarkable releases of iodine from solid samples do not occur before 700 C, and a temperature of more than 800 C does not further increase the releases of iodine from solid samples. 32 Practically, 800 C was oen applied for the combustion of samples and vaporization of iodine.…”
Section: Effective Vaporization Of Iodine In the Pyrolysis Of Vegetatmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest electrodeposition of 252 Cf ever produced at the REDC included 6.3 ± 0.5 GBq (1.7 ± 0.1 Ci) 252 Cf [3], [4], but the source was thicker than desired for the application, which resulted in reduced overall fission fragment yield. This is believed to originate from the electrodeposition procedure, in which the organic substituents from the ammonium acetate electrolyte solution are deposited along with 252 Cf.…”
Section: Introductionmentioning
confidence: 99%